Wortarten und Pronomina. Studien zur lettischen Grammatik - Nau, Nicole (Wydział Neofilologii UAM w Poznaniu, 2016)
This book investigates the nature of pronouns as a part-of-speech in Latvian grammar. It is argued that the set of words called pronouns in traditional Latvian grammar is best seen not as a word-class, but as cluster of several small closed classes that are defined by functional criteria. Grammatical features are spread across these classes in a non-random way. This gives the cluster a structure that can be visualized as a map where particular features are shared by neighboring elements. Discussions about the nature and status of word-classes and of pronouns in general linguistics, especially of the late 20th century, form the background of this study. The problems pronouns have posed for descriptive linguistics are illustrated by a comparison of descriptive grammars of German, English, Russian, and French. In addition to a detailed description of grammatical characteristics of Latvian pronouns, the book includes a general outline of the grammar of modern Latvian, describing the syntax of clauses and noun phrases, inflectional morphology and the structure of words, and the main characteristics of verbs, nouns, and adjectives. The empirical study is based on a collection of spoken and written Latvian texts, and data are presented with interlinear morphological glosses.
Keywords: Latvian; pronouns; part-of-speech; word-class; morphology; syntax; język łotewski; zaimki; części mowy; morfologia; składnia